Facilities and Infrastructure Management in Implementing National Education Standards at SMP Negeri 35 Medan - Fadilla, Anggun Sari; Syukri, Makmur (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract. Facilities and infrastructure are important things to pay attention to so that the learning process in schools can be carried out well, effectively and efficiently, the facilities and infrastructure in schools must be in accordance with the educational standards set by the government. This research aims to find out whether the existing facilities and infrastructure at SMP Negeri 35 Medan are in accordance with existing National education standards, or whether there are still several standards or management of educational facilities and infrastructure that have not yet been implemented or carried out as they should. The results of the observations show that the facilities and infrastructure management process is (1) planning educational facilities and infrastructure, (2) procurement of educational facilities and infrastructure, (3) maintenance of educational facilities and infrastructure, (4) inventory of educational facilities and infrastructure, and (5) Elimination of educational facilities and infrastructure, it turns out that from the 5 existing management processes, there are several procedures that must be paid attention to at SMP 35 Medan so that they can be carried out in accordance with existing procedures, so that later the learning process at SMP 35 Medan can be carried out in accordance with standards. existing national education. Facilities and infrastructure management process. This research was carried out using qualitative phenomenological methods so that the data obtained was more accurate.Keywords: management; standards for educational facilities; infrastructure